2020
DOI: 10.1101/2020.07.26.20162206
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Mobile Cabin Hospital compulsory quarantine for mild patients was an alternative method to combat COVID-19: the Chinese experience

Abstract: Background: Since the end of 2019 to the present day, the outbreak of the coronavirus disease 2019 (COVID-19) has had an immense impact on China and on other countries worldwide. This outbreak represents a serious threat to the lives and health of people all around the world. The epidemic first broke out in Wuhan, where the Chinese government was unable to prevent the spread of the disease by implementing home quarantine measures. Mobile cabin hospitals were used to relieve pressure on hospitals due to the nee… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 23 publications
0
4
0
Order By: Relevance
“…The Chinese government mobilised 346 medical teams—a total of 42 600 medical staff and 900 public health professionals—to support Wuhan city and Hubei province. Two new hospitals were rapidly constructed to provide an extra 2600 beds while 16 mobile cabin hospitals with 14 000 beds were designated for mandatory quarantine of patients with mild disease 25…”
Section: Mobilising Resourcesmentioning
confidence: 99%
“…The Chinese government mobilised 346 medical teams—a total of 42 600 medical staff and 900 public health professionals—to support Wuhan city and Hubei province. Two new hospitals were rapidly constructed to provide an extra 2600 beds while 16 mobile cabin hospitals with 14 000 beds were designated for mandatory quarantine of patients with mild disease 25…”
Section: Mobilising Resourcesmentioning
confidence: 99%
“…The worldwide outbreak of the COVID-19 pandemic has presented unparalleled challenges to the field of medical and nursing practices. Mobile cabin hospitals, alternatively refer to as Fangcang shelter hospitals, modular hospitals, or field hospitals, assume a pivotal role in addressing extensive epidemics and delivering essential medical services to a substantial population of COVID-19 patients ( Chen et al, 2020 ; Li et al, 2022 ). However, mobile cabin hospitals frequently encounter formidable challenges, including a scarcity of medical resources, demanding work schedules, and secluded environments, which not only evoke apprehension among medical personnel regarding their health risks but also significantly impact their mental state and behavior.…”
Section: Introductionmentioning
confidence: 99%
“…As a cost-effective and easy-to-build modular medical facility, SCH provides essential functions such as isolation, triage, basic medical services, regular monitoring, and rapid diagnosis. Numerous studies have shown that SCH can increase patient admission rates, contain epidemics, and reduce the rate of mild and moderate cases progressing to severe and critical cases, effectively slowing down the spread of COVID-19 (12)(13)(14)(15).…”
Section: Introductionmentioning
confidence: 99%